The Efficacy of Using Passive Voice Cards in Teaching Grammar - Shanty Halim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research aims at finding out the efficacy of using passive voce cards in teaching grammar, especially the passive voice to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of the passive voice cards effective in teaching passive voice to Indonesian EFL students?.  The research can be an addition to the persisting teaching grammar of English particularly the passive voice through the use of the passive voice cards.  This research was conducted at the the student at Politeknik Negeri Ujung Pandang, an Indonesian Vocational Higher Education. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering conditional sentences and the post-test given to find out the students’ improvement in mastering passive voice after giving the treatment by using of passive voice cards.  The findings show that using the passive voice cards is effective in teaching conditional sentences to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00.  Therefore, it is recommended to use the pair work technique in developing students’ competence in mastering passive voice of Indonesian EFL students.